Tecnicas de combate de Taiji, Xingyi y Bagua - Juan Carlos Serrato Rodríguez (Universidad de León, 2012)
Lu Shengli. Barcelona: Paidotribo, 2009 (1ª ed.). 305 paginas. 27,5x21,5 cm. I.S.B.N: 974-84-8019-170-8.